2010
DOI: 10.1007/s00128-010-9971-6
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Variations of Heavy Metals in Surface Sediments in Bohai Bay, North China

Abstract: Characteristics of the spatial and temporal distributions of selected heavy metals (Cu, Zn, Cd, Pb and Hg) in Bohai Bay, north China was examined. Surface sediment samples from 15 sites were collected and analyzed for the selected metals with atomic absorption spectrometry (AAS) from the year of 1997-2007. Mean concentrations of metals in the 11-year period showed that Hg and Zn concentrations slightly fluctuated, while Cu, Cd and Pb concentrations in sediments varied with time. High levels of heavy metals occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…The data of an 11-year monitoring program from 1997 to 2007 indicated that the mean concentrations of Cd, Cu, Hg, Pb and Zn in the surface sediments of the Bohai Bay were all within the range for MSQ Grade I, but all higher than the corresponding background values of sediments in this area (Table 2; Zhan et al, 2010). This indicated that these metals did increase to some extent due to the influence of human activities, although their concentrations were still within relatively satisfactory levels.…”
Section: The Situation Of the Bohai Baymentioning
confidence: 97%
See 1 more Smart Citation
“…The data of an 11-year monitoring program from 1997 to 2007 indicated that the mean concentrations of Cd, Cu, Hg, Pb and Zn in the surface sediments of the Bohai Bay were all within the range for MSQ Grade I, but all higher than the corresponding background values of sediments in this area (Table 2; Zhan et al, 2010). This indicated that these metals did increase to some extent due to the influence of human activities, although their concentrations were still within relatively satisfactory levels.…”
Section: The Situation Of the Bohai Baymentioning
confidence: 97%
“…The combined effects of riverine and atmospheric sources may be responsible for higher concentrations of some trace metals in sediments occurring not only along the shoreline but also in the inner part of the Bohai Bay (Zhan et al, 2010).…”
Section: The Situation Of the Bohai Baymentioning
confidence: 99%
“…Coastal and estuarine ecosystems can play a significant role as reservoirs for many persistent organic and inorganic contaminants, such as nutrients and trace elements, through adsorption onto suspended matter and subsequent sedimentation (Zhan et al, 2010;Junakova et al, 2015). The main sources of contamination in estuaries are derived from catchment area runoff and include mining, industries, commercial waste, urban development, sewage discharge, agricultural and irrigation runoff, and atmospheric deposition (Karageorgis et al, 2012;Cheng et al, 2015;Singovszka et al, 2015;Kim et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The accumulation of pollutants can be greater in enclosed and semi-enclosed areas where the exchange of water with the open seas is limited (Karageorgis et al, 2002). The watershed and estuarine environment has experienced dramatic reductions in species diversity and abundance, diseases in marine-cultured species, and habitat loss, which will ultimately destroy marine ecosystem structures and functions, and affect the health of human beings profoundly.Metals contamination of Bohai Sea have been investigated over the past few years (Feng et al, 2011;Meng et al, 2008;Wang and Wang, 2007;Zhan et al, 2010), however, almost all previous studies have focused on downstream areas (coastal and estuarine systems, namely marine and saline water systems), such as the estuaries, the coasts and the bays along the Bohai Sea. The spatial distribution of arsenic (As) and metals as well as the corresponding environmental risks within the coastal watersheds in upstream areas (surface water systems, namely freshwater systems), especially in southern Bohai Sea, have received less attention.…”
mentioning
confidence: 99%
“…Metals contamination of Bohai Sea have been investigated over the past few years (Feng et al, 2011;Meng et al, 2008;Wang and Wang, 2007;Zhan et al, 2010), however, almost all previous studies have focused on downstream areas (coastal and estuarine systems, namely marine and saline water systems), such as the estuaries, the coasts and the bays along the Bohai Sea. The spatial distribution of arsenic (As) and metals as well as the corresponding environmental risks within the coastal watersheds in upstream areas (surface water systems, namely freshwater systems), especially in southern Bohai Sea, have received less attention.…”
mentioning
confidence: 99%